Contemporary use and social importance of the post-industrial heritage in the Kamienna river valley (Poland) - Kulawiak, Anita (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2021)
The aim of the article is to identify the industrial heritage located in the valley of the Kamienna river (Poland), and in particular to examine its current use and the importance it plays in the minds of the inhabitants of the communes included in the studied area. The empirical basis of the study was the research carried out in the period from July to September 2019, consisting of both participant observation, field inventory and a questionnaire interview conducted with the inhabitants of the studied communes. The collected material revealed that this area, despite the passage of years, has a rich and unique post-industrial potential in Poland, which is a testimony to its rich and long history. Although today the importance of the industrial function in the Kamienna valley is much smaller, the legacy preserved there has enormous economic, cultural and social potential. Currently, however, its capabilities are not fully used, mainly due to the human factor.